2016
DOI: 10.3390/ma9050362
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bonding Shear Performance of Ultra-High-Performance Concrete with Increase in Delay in Formation of Cold Joints

Abstract: This study set out to derive the optimal conditions for ensuring the monolithicity of ultra-high-performance concrete (UHPC). Direct shear tests were performed to examine the influence on the bonding shear performance. The experimental variables included tamping and delay, which were set to 0, 15, 30, and 60 min. SEM and XRD analyses of the microstructure and composition were performed. The direct shear tests showed that the bonding shear strength was enhanced by the addition of tamping. For the normal-strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…UHPC contains a large quantity of unreacted cement clinkers despite the HT [ 12 , 14 , 31 , 32 ]. This is primarily because there is an insufficient amount of water for the complete hydration of the cement [ 7 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…UHPC contains a large quantity of unreacted cement clinkers despite the HT [ 12 , 14 , 31 , 32 ]. This is primarily because there is an insufficient amount of water for the complete hydration of the cement [ 7 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The uppermost layer apparently contains hydration products that cause early densification. Similarly, Lee et al [29] observed a smooth surface which can cause some cold-joint issues during the casting process of UHPC. They concluded that the film formed on the casting surface consists of SiO 2 crystalline structures and that this is the cause of the degradation of the bonding performance in terms of cold-joint formation.…”
Section: Sem Observationsmentioning
confidence: 86%
“…For different structural applications, such as repairing and strengthening old concrete structures or connecting full-depth deck panels using closure joints [53,54], casting UHPC next to concrete at different ages or even casting UHPC next to steel [55] highlights the challenge of bond strength between these two materials. A bi-surface shear test setup was selected to measure the bond strength for smooth and rough interface surfaces between the two materials to quantify the interfacial bond strength between UHPC and NSC [56,57].…”
Section: Bond Strength Testmentioning
confidence: 99%